MODEL PEMBELAJARAN INOVATIF BERBASIS FLIPPED CLASSROOM DALAM PENGAJARAN ENGLISH GRAMMAR - I Putu Edi Sutrisna (Padma Sari: Jurnal Ilmu Pendidikan, 2022)
The problem of learning English grammar in EFL countries has triggered the emergence of various innovative learning models. One of them is an innovative learning model called the Flipped Classroom. Through a literature review, this article has found that this learning model focuses on content and learning activities that are provided online to students first so that they get access to materials regarding learning English before attending the class. Therefore, when they attend the actual class, they will fully understand the learning material regarding the structure of the language to be delivered. In addition, it was also found that, from an empirical study by several researchers, the Flipped Classroom was proven to be effective for learning English grammar at the elementary, middle, or even higher education levels where this model was able to motivate students to learn more independently and meaningfully through the help of information technology media. Seeing the effectiveness of Flipped Classrooms in teaching English grammar in EFL countries, it can be assumed that this method can be one of the most effective and useful learning models in teaching English grammar